Effect of green propolis on the productivity, nutrient utilisation, and intestinal morphology of Japanese laying quail - Pieroni,Carolina Alves (2020)
ABSTRACT In this study, we evaluated the effects of dietary inclusion of ethanolic extract of green propolis (EEGP) on productivity, egg quality, nutrient utilization, and duodenal morphology of 120 Japanese laying quail. The quail were randomly distributed into five treatment groups: one group with no EEGP in the diet (control diet) and four groups with increasing EEGP levels (500, 1000, 1500, and 2000 mg EEGP/kg diet) in the diets. Excreta and diet samples were collected on day 40 and were analyzed for dry matter (DM), crude protein (CP), ether extract (EE), ash, gross energy (GE), calcium, and phosphorus to evaluate the nutrient and energy use. At the end of the study period, productive performance, egg quality, and duodenum morphology were evaluated. Duodenal sections were obtained from four birds per treatment and were processed for optical microscopy. The EEGP did not affect DM, GE utilization, apparent metabolizable energy, ash retention, feed intake, feed conversion, egg mass, egg quality, crypt depth, or villus height:crypt depth ratio in the duodenum. However, EEGP did increase laying rate, CP, EE, calcium, and phosphorus utilization, as well as villus height and absorption surface area in the duodenum when provided to birds at 1500 and 2000 mg/kg in the diet. Thus, the inclusion of EEGP at 1500 ppm in the diet of Japanese laying quail improves productivity, egg quality, nutrient utilization ability, and duodenal morphology.